Translation with Extrinsic Aspect Approach in the Form of Pragmatics and Modulation Translation Method - Wuri Syaputri; Akbar Fi Rizky; Widyasari Widyasari; Yudi Efendi (Universitas Lancang Kuning, 2023)
The following study aims to examine the extrinsic elements in the form of pragmatics contained in the catchphrase